Diseño de una propuesta de manejo para la microcuenca del Rio Guargualla ubicada en la Parroqia Cebadas, Cantón Guamote, Provincia de Chimborazo. - Salgado, Yessenia (2013)
The present research work is a design of a management proposal for Guarguallá river watershed, this study aims to diagnosis the current state of the watershed, qualitatively and quantitatively assess , the environmental impacts in order to structure and develop a proposal for management to achieve the objectives interviews and surveys were applied, we performed flow measurement at four points using the float method, we analyzed chemical parameters in water and soil samples for the determination of results and conclusions were tabulated statistically data, determining the degree of water pollution was made by ICA (water quality index), the Leopold matrix was used for the assessment of environmental impacts.